Step by step management of male infertility - Pandya, Manish R. (Jaypee Brothers Medical Publishers, 2008)
Infertility is simply inability to conceive by a couple inspite of regular normal coitus by the couple involved. Management of mail infertility plays a key part in the practice of total infertility management. This book informs about assessing an infertile couple both by a gynecologist and an andrologist to diagnose accurately for treatment. Informs about development of in vitro fertilization technique to treat both male and female infertility.